“Soaring Towards the Sun”: The Icarus Complex in Daphne Du Maurier’s The Flight of the Falcon - Helena Habibi (Revue LISA)
Bird-men, compelled fatefully to soar sun-ward, haunt Daphne Du Maurier’s novels and short stories. Her incessant re-working of the myth of Icarus finds its climax in her later novel, The Flight of the Falcon (1965), in which Aldo Donati dons Daedalus-like wings, then, “like Icarus, […] fl[ies] too near the sun” before plummeting to his death. Furthermore, the presentation of the novel’s Donati brothers reflects, with uncanny accuracy, components of Jungian symbology as well as the “Icarus complex”, first identified by psychologist, Henry A. Murray. This article examines the relatively critically neglected novel, The Flight of the Falcon, as a narrative transformation of the classical myth of Icarus and the psychoanalytic theories that it inspired. In doing so, the article seeks to dispel du Maurier’s own anxiety that the “deep unconscious motive[s]” underlying the macabre actions of her beguiling, bird-imitating protagonist, Aldo Donati, and his brother, Armino, would remain overlooked.